Hypovitaminosis D in adult patients scheduled for orthopaedic surgery: a cross-sectional and observational study - Abbas, Gazala; Dagoria, Sparsh; Yasin, Asma; Afzal, Tahir; Bhat, Abdul M.; Atri, Nikhil (International Journal of Research in Orthopaedics, 2026)
Background: Hypovitaminosis D is a common yet underdiagnosed nutritional deficiency with significant implications for orthopaedic surgical patients. Vitamin D plays a critical role in calcium homeostasis, bone metabolism, and muscle function—factors influencing bone healing, infection risk, and postoperative rehabilitation. Although global studies report high prevalence, limited Indian data exist for orthopaedic surgery patients. Methods: A cross-sectional observational study was conducted in the Department of Orthopaedics, Government Medical College, Jammu, from September 2023 to February 2024. Fifty adult patients (>20 years) scheduled for elective orthopaedic surgery were included. Serum 25-hydroxyvitamin D (25(OH)D) levels were measured preoperatively using liquid chromatography–tandem mass spectrometry. Deficiency was defined as <20 ng/ml, insufficiency as 20–30 ng/ml, and optimal as >30 ng/ml. Demographic and clinical variables (age, sex, BMI) were recorded. Ethical clearance was obtained from the Institutional Ethics Committee (approval no. GMCJ/IEC/2023/241). Results: Mean age was 56.17±15.23 years; 58% were male. Mean body mass index (BMI) was 25.61±4.21 kg/m², with 38% overweight. Vitamin D deficiency was present in 30% of patients, insufficiency in 40%, and optimal levels in 30%. Deficiency was more prevalent among males and overweight individuals, and highest in the 61–70-year age group (38%). Conclusions: Hypovitaminosis D is highly prevalent among adults undergoing orthopaedic surgery. Overweight status and male gender were associated with higher risk. Routine preoperative screening and supplementation could improve surgical outcomes and reduce complications.